THE RELATIONSHIP BETWEEN AUTHORITARIAN PARENTING AND CAREER PLANNING (Correlation Study on Class XI Students of Motorcycle Engineering Department at Vocational High School) - Choirunnisa, Choirunnisa; Muhibah, Siti; Khairun, Deasy Yunika (Jurusan Bimbingan dan Konseling, 2024)
This research is a quantitative approach with a correlation research method, which explains how the relationship between two variables, this research discusses the influence of parental authoritarian parenting on student career planning. The purpose of this study is to reveal the relationship between authoritarian parenting by parents on students' career planning. The research data collection method uses a questionnaire consisting of questionnaires for two variables. The questionnaire used in this study uses a Likert scale. The sampling technique uses the Total Sampling technique. The sample used in this study amounted to 72 students in class XI of the Motorcycle Engineering Department of Vocational High School Regency in the 2023/2024 school year. The results of this study indicate that parental authoritarian parenting has a negative relationship to student career planning. This is shown through the results of the Pearson product moment correlation test analysis with the correlation value of the two variables which is r = -0.709, stating that there is a strong relationship between the two variables. Furthermore, the value of determination (R Square) is 0.503, this value states that authoritarian parenting (X) has an effect of 50.3% on student career planning (Y). Based on the results of the study, researchers provide suggestions for counseling teachers and parents to create a service programme to educate parents and students about the influence of parental parenting on student career planning. The suggestion for further research is to conduct research to find other aspects that influence student career planning.